OP38 Objectively measured physical activity and sedentary time: cross-sectional and prospective associations with adiposity in the Millennium Cohort Study. (13th September 2016) - Griffiths, LJ; Sera, F; Cortina-Borja, M; Law, C; Ness, A; Dezateux, C
Abstract : Background: There is limited evidence on the prospective associations of activity levels with adiposity indicators in young people. This study assessed whether physical activity (PA) and sedentary time (ST) in primary school-aged children are associated with adiposity at the start of secondary school, and whether these associations differed by sex or ethnic group. Methods: We analysed data from the Millennium Cohort Study, a longitudinal study of social, economic and health-related circumstances of children born in the United Kingdom between September 2000 and January 2002. At the fourth contact, when the Cohort were aged 7, PA and ST were assessed objectively using Actigraph GT1M accelerometers. Valid data (2 days with ≥ 10 hours of recorded time) was obtained from 6497 singleton children. These data were used to derive average daily minutes of moderate-to-vigorous physical activity (MVPA), average daily minutes spent in ST and total physical activity. Measures of adiposity (body mass index (BMI), fat mass index (FMI) and fat free mass index (FFMI)) were obtained at seven and 11 years of age. Results: In cross-sectional analyses, total PA levels were inversely associated with FMI (3.7% (95% confidence interval (CI): 2.7; 4.7) reduction per 150 cpm increase), as was MVPA (4.2% (CI: 3.2; 5.2) reduction per 20 minute/day increase). Associations were stronger in Black and South Asian ethnic groups. Total PA and MVPA were not associated with FFMI. ST was positively associated with FMI (1.3% (CI: 0.2; 2.3) increase per 50 minute/day increase) and inversely associated with FFMI (0.5% (CI: 0.2; 0.7) reduction per 50 minute/day increase). Longitudinally, MVPA at age seven remained inversely associated with FMI at age 11 (1.5% (CI: 2.6; 0.4) reduction per 20 minute/day increase). No association was found between total PA and ST and any of the later adiposity measures. Conclusion: Seven year old children who are more physically active are less likely to be obese at that age and at age eleven years. These associations were particularly evident in children from Black or South Asian ethnicity at age seven and in boys at age 11; these findings highlight the importance of promoting higher levels of physical activity in primary school-aged children. Measurements of fat mass also provide valuable insights into ethnic differences in associations between activity and adiposity.